Wheat Cost-Return Budget in Northeast Kansas - Lubben, Bradley D.; Staggenborg, Scott A. (My University, 2001)
This publication projects a budget that reflects expected income and costs based on wheat production in northeastern Kansas.
MF572_2001_10
Keywords: MF572; Economics; Crops; MF